Multiple Solutions for Biharmonic Equations with Asymptotically Linear Nonlinearities. (27th May 2010) - Pei Pei, Ruichang Ruichang
Abstract : The existence of multiple solutions for a class of fourth elliptic equation with respect to the resonance and nonresonance conditions is established by using the minimax method and Morse theory.